The impact of psychological aspects, age, and BMI on eating disorder psychopathology among adult males and females with type 1 diabetes. Issue 2 (November 2020) - Wisting, Line; Siegwarth, Cecilie; Skrivarhaug, Torild; Dahl-Jørgensen, Knut; Rø, Øyvind
This study investigated correlates of eating disorder (ED) psychopathology among adults with type 1 diabetes (T1D). A total of 282 males ( n = 112) and females ( n = 170) with T1D (18–79 years) participated. Overall, psychological aspects (i.e. illness perceptions, coping strategies, insulin beliefs, anxiety, and depression) were associated with ED psychopathology. Associations were generally stronger among females than males. In a regression model, age, BMI, personal control, and anxiety explained 51% of the variance in ED psychopathology among females, whereas BMI, personal control, and anxiety explained 47% of the variance among males. Greater clinical awareness of health psychological aspects may contribute to reduce the risk of developing ED.